Comparative Proteome Analysis of Shewanella putrefaciens WS13 Mature Biofilm Under Cold Stress - Yan, Jun; Xie, Jing (Frontiers in Microbiology, 2020)
Worldwide, Shewanella putrefaciens is the predominant seafood spoilage microorganism during cold storage. This bacterium can attach to biotic/abiotic surfaces to form biofilms which contribute to seafood quality degradation and shelf-life reduction. The mechanism of S. putrefaciens biofilm formation is not yet described. Crystal violet staining in combination with confocal laser scanning microscopy (CLSM) was used to study the sequence of events leading to the establishment of a mature biofilm at 4, 15, and 30°C. In addition, the main chemical constituents of the mature biofilm were determined by Raman spectroscopy (RM), whereas, comparative proteomic analysis was used to quantify changes in metabolic pathways and to find out underlying protein determinants. The physical dimensions of the mature biofilm, i.e., biomass, biovolume, and mean thickness, were higher at 4°C when compared to 15 and 30°C. The variations of proteins measured by RM confirmed the importance of proteins during the formation of a mature biofilm. Comparative proteomic analysis showed that siderophore and iron chelate transport proteins were down-regulated during mature biofilm formation. The down-regulated aforementioned proteins are involved in promoting iron storage in response to a higher demand for metabolic energy, whereas, the upregulated proteins of the sulfur relay system, pyrimidine metabolism, and purine metabolism are related to bacterial adaptability. Synthesis of proteins related to cold stress was increased and proteins involved in aminoacyl-tRNA biosynthesis were up-regulated, whereas, proteins involved in aminopeptidase activity were down-regulated. Proteolysis to scavenge energy was reduced as proteins involved in pyrophosphatase activity were up-regulated. Also extracellular eDNA was found which may play an important role in maintaining the stability of mature S. putrefaciens biofilm structures under cold stress. This work provides a better understanding of the role of proteins in mature biofilms. In addition, the biofilm formation mechanism of a psychrotrophic spoilage bacterial species at low temperature is explored, which may contribute to generating biofilm controlling strategies during seafood preservation and processing.